(untitled) (Journal of Social Sciences Review, 2025)
This article examines how human subjectivity is impacted by capitalism through the perspectives of two significant intellectuals, Marx and Weber. Marx analyzes capitalism’s effects by focusing on the alienation it causes. He argues that humans are inherently productive and interact with each other to fulfill their basic needs, making them inherently social. According to Marx, capitalism creates a separation between individuals and their labor, leading them to feel disconnected from their own creation. Conversely, Weber approaches capitalism from a different perspective. He critiques the system based on its formal rationality, influenced by Nietzsche’s sense of cultural disenchantment. Weber highlights how capitalism’s emphasis on rationality and efficiency can impact human experiences and values. In Max Weber’s canon, rationality has been acknowledged as possibly the central theme. Practical, theoretical, substantive, and formal rationality are recognized as four different types of rationality. According to Weber, the prominence of formal and theoretical rationality should be attributed to the capitalist system.